GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 2711 species occurrences available in GBIF matching the query: TaxonKey: Mazama Rafinesque, 1817 HasCoordinate: true HasGeospatialIssue: false. The dataset includes 2711 records from 64 constituent datasets: 33 records from MVZ Mammal Collection (Arctos). 35 records from KUBI Mammalogy Collection. 2 records from MLZ Mammal Collection (Arctos). 10 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 5 records from Mamíferos de la colección del Instituto Alexander von Humboldt. 18 records from Inventario de fauna presente en la jurisdicción de Corantioquia. 121 records from Field Museum of Natural History (Zoology) Mammal Collection. 4 records from Museum of Comparative Zoology, Harvard University. 39 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 2 records from Colección de mamíferos del Museo de Historia Natural de la Pontificia Universidad Javeriana. 21 records from iNaturalist Research-grade Observations. 86 records from Colección Nacional de Mastozoología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 29 records from Mammals housed at MHNG, Geneva. 67 records from NMNH occurrence DwC-A. 11 records from DMNS Mammal Collection (Arctos). 4 records from Cruzando el Caribe - Construyendo la capacidad para el ecoturismo en el Darién y Urabá. 2 records from Colección de mamíferos de la Universidad del Valle. 6 records from naturgucker. 1 records from CAS Mammalogy (MAM). 31 records from UMMZ Mammal Collection. 3 records from LACM Vertebrate Collection. 1 records from Macaulay Library Audio and Video Collection. 26 records from Computarización de la Colección Nacional de mamíferos del Instituto de Biología, UNAM. 1 records from Distribución geográfica de las aves y los mamíferos del estado de Querétaro. 1 records from Distribución geográfica de las aves y los mamíferos de las zonas montanas de los estados de San Luis Potosí e Hidalgo circundantes de la Sierra Gorda. 3 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. Mamíferos. 4 records from Inventario de la biodiversidad de vertebrados terrestres de los Chimalapas, Oaxaca. 1 records from Computarización de las colecciones de vertebrados terrestres de la Escuela Nacional de Ciencias Biológicas, IPN - Fases 3. 4 records from Anfibios, reptiles y mamíferos del corredor biológico del norte de Yucatán depositados en las colecciones de la Escuela Nacional de Ciencias Biológicas. 32 records from Sistematización de las colecciones científicas del Instituto de Historia Natural y Ecología, (IHNE) Chiapas. 17 records from Vertebrados terrestres del Corredor Biológico Sierra Madre del Sur, Chiapas, México. 41 records from Actualización de la base de datos de la colección mastozoológica de El Colegio de la Frontera Sur, San Cristóbal de las Casas. 90 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 4 records from Inventario de los mamíferos de las reservas de la biósfera Mapimí, La Michilía, El Cielo y Calakmul. 6 records from Incorporación de nuevos registros de mamíferos de la región Sierra Norte de Oaxaca. 61 records from Actualización de la base de datos del Atlas Mastozoológico de México. 2 records from RBINS collections. 1 records from UWBM Mammalogy Collection. 9 records from UF Florida Museum of Natural History Mammals. 36 records from NYSM Mammals. 3 records from Colección Mastozoológica de la Universidad Industrial de Santander. 12 records from LSUMZ Mammals Collection. 22 records from Paleobiology Database. 30 records from CNMA/Colección Nacional de mamíferos. 1 records from Mammal specimens. 2 records from Vertebrate Zoology Division - Mammalogy, Yale Peabody Museum. 8 records from TTU Mammals Collection. 4 records from Colección de Mamíferos del Museo de Zoología 'Alfonso L . Herrera', México (MZFC, UNAM). 2 records from Caracterización de fauna y flora para el establecimiento de límites funcionales de humedales en tres ventanas piloto: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo de humedales Paz de Ariporo - Hato Corozal. 1 records from Colección Teriológica y Ornitológica de la Universidad Tecnológica del Chocó. 1 records from CNMA/Colección de Mamíferos de la Estación de Biología Los Tuxtlas. 7 records from AMNH Mammal Collections. 1 records from Mamíferos voladores y no voladores del suroccidente colombiano. 1 records from Mammal Specimens. 745 records from Avistajes de espcies de valor especial en áreas protegidas del noreste de Argentina. 17 records from Geographically tagged INSDC sequences. 11 records from MSB Mammal Collection (Arctos). 30 records from Mammalogy Collection - Royal Ontario Museum. 1 records from Análisis ecológico de la mastofauna en la parte alta del Rio Güangui. 5 records from Instituto de ciencias naturales. 711 records from VERTEBRADOS DE VALOR ESPECIAL EN ÁREAS PROTEGIDAS DE LA ARGENTINA. 55 records from Occurrences in SinBIOTA. 1 records from Angelo State Natural History Collections (ASNHC) - Mammalogy Collection. 170 records from USAC Mammals Collection.
Keywords: GBIF; biodiversity; species occurrences